Background of Peruvian gastronomy and its perspectives: an assessment of its current growth - Joaquín Aguirre-Sosa; Maria Luisa Dextre; Michellle Lozada-Urbano; Jorge Alberto Vargas-Merino (Journal of Ethnic Foods, 2023)
Abstract Peruvian gastronomy is continuously expanding throughout the world, captivating various regions and major cities with its flavors, textures, colors, and culinary excellence. The objective of this research is to describe the background of Peruvian gastronomy and its perspectives, in order to assess its current growth. A bibliographic and exploratory analysis was conducted, delving into its significance throughout history. The culinary background was delineated from the Pre-Inca, Inca, Colonial, Republican eras, up to the present day. Additionally, the perspectives from the government, private sector, and citizens were explored to evaluate the current status achieved worldwide. Given the importance of the current position held by Peruvian gastronomy, this study holds international relevance in assessing our legacy and paying tribute to the individuals from the past, present, and future whose strategic work enables the expansion of the Peruvian gastronomy. It is concluded that Peruvians must continue striving for continuous improvement in the key links of our gastronomy’s production chain.